2003
DOI: 10.1037/0278-6133.22.5.504
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of disease severity and perceptions of primary and secondary control to the prediction of psychosocial adjustment to Parkinson's disease.

Abstract: Seventy-four people with Parkinson's disease (PD) completed questionnaires and were interviewed to determine the degree to which the severity of PD and perceptions of primary and secondary control over PD predicted psychosocial adjustment. Significant unique contributions to PD-related participation restrictions were made by disease severity (positive relationship) and perceived internal secondary control (negative relationship). Also, participation restrictions had a significant direct effect, and disease sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
1
28
1
Order By: Relevance
“…The research question and methods build on past research, first, by breaking down both control and SWB into their constituent parts and examining how different parts relate to one another, lending greater precision and nuance to our understanding of each. Second, as one of the few studies that looks at the link between control strategies and SWB in an everyday context, this work advances research on primary and secondary control beyond the realm of clinical outcomes or adjustment to major life stressors (e.g., Affleck, Allen, Tennen, McGrade, & Ratzan, 1985;Grootenhuis, Last, Graaf-Nijkerk, Johanna, & Van Der Wel, 1996;McQuillen, Licht, & Licht, 2003), documenting a role for each in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…The research question and methods build on past research, first, by breaking down both control and SWB into their constituent parts and examining how different parts relate to one another, lending greater precision and nuance to our understanding of each. Second, as one of the few studies that looks at the link between control strategies and SWB in an everyday context, this work advances research on primary and secondary control beyond the realm of clinical outcomes or adjustment to major life stressors (e.g., Affleck, Allen, Tennen, McGrade, & Ratzan, 1985;Grootenhuis, Last, Graaf-Nijkerk, Johanna, & Van Der Wel, 1996;McQuillen, Licht, & Licht, 2003), documenting a role for each in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this postulation, Myers and Myers (1999) found that control by physicians explained a substantial portion (35%) of the variance in treatment adherence amongst patients with cystic fibrosis. In addition, some researchers have posited that control by health professionals and control by non-health professionals represent relatively independent dimensions (e.g., Billington, Simpson, Unwin, Bray, & Giles, 2008; McQuillen, Licht, & Licht, 2003), but only a few studies have used separate subscales to assess these two sources of interpersonal control (e.g., Billington et al, 2008; De las Cuevas, Peñate, & Sanz, 2014). Further effort should be made to distinguish the benefits and costs of these sources of interpersonal control after more studies have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Although enlightening, these studies do not permit comparisons of strategies across multiple domains, nor do they allow for the analysis of both primary and secondary control strategies. A third limitation is that different types of health problems have not been directly compared; studies have instead concentrated on individuals with specific chronic conditions, such as arthritis (Chipperfield & Greenslade, 1999;Hampson, Glasgow, & Zeiss, 1994), cancer (Arraras, Wright, Jusue, Tejedor, & Calvo, 2002;Carver et al, 1993;Taylor, Lichtman, & Wood, 1984), chronic back pain (Grant, Long, & Willms, 2002), diabetes (Band & Weisz, 1990), HIV (Thompson et al, 1994), or Parkinson's disease (McQuillen, Licht, & Licht, 2003).…”
Section: Empirical Research On Primary and Secondary Controlmentioning
confidence: 99%